If the Coast Guard is the Solution, What is the Problem?. Issue 1 (8th January 2021) - Triner, Donald; Kaufman, Roger
Abstract: This essay applies a methodology of strategic thinking through the use of the Organizational Elements Model (Kaufman, 1996) and adding value to society (Mega level thinking). The essay analyzes the Commandant's Direction for the US Coast Guard with this framework. It includes examples of an Ideal Vision and Mission Objective for the US Coast Guard, as well as a description of the process of increasing the utility of an organization's strategic plan. We wrote this article in the 1996–1997 timeframe. It was never published.